Answer:
Step-by-step explanation:
Let the first number = x
Let the second number = x + 9
Let the third number = 4x
Together they make 123
x + x + 9 + 4x = 123 combine the left
6x + 9 = 123 Subtract 9 from both sides
6x = 123 - 9
6x = 114 Divide by 6
x = 114/6
x = 19
=================
First number = 19
Second number = 19 + 9 = 28
Third number = 4*19 = 76
A. The figure is a triangular pyramid. You can findits surface area by adding up the area of the three faces of the triangle and the area of the base. A derived formula also is used where the SA is equal to 12 times the perimeter of base times the slant height, added to that is the area of the base. The area of the square base is s^2. Its perimeter is 4s.
SA of Pyramid = 12*P*l + s^2
SA of Pyramid = 12*4s*l + 16^2
SA of Pyramid = 12*4(16)*(17) + (16)^2
SA of Pyramid = 11,008 square inches
b.) The formula for the SA of a cone is:
SA of cone = πr[r+√(h^2+r^2)]
SA of cone = π(3)[(3+√(8^2+3^2)]
SA of cone = 108.8 square inches
Answer:
B
Step-by-step explanation:
Answer: -62
Step-by-step explanation:
9( a + 2b) + c
Substitute correct values for all a, b and c.
9( -3 + 2(-2) ) + 1
9( -3 - 4 ) + 1
9(-7) + 1
-63 + 1
-62.
Answer:
k = 0.25
Step-by-step explanation:
The standard equation of a proportional relationship is
y = kx ← k is the constant of proportion
y = 0.25x ← is in this form
with k = 0.25